2022
DOI: 10.21203/rs.3.rs-2368979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of equatorial plasma bubble after the 2022 Tonga volcanic eruption

Abstract: Equatorial plasma bubbles are a phenomenon of plasma density depletion with small-scale density irregularities, normally observed in the equatorial ionosphere. This phenomenon, which impacts satellite-based communications, was observed in the Asia-Pacific region after the largest-on-record January 15, 2022 eruption of the Tonga volcano. We used satellite and ground-based ionospheric observations to demonstrate that an air pressure wave triggered by the Tonga volcanic eruption could cause the emergence of an eq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 75 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…The study by Shinbori et al. (2023) showed that TEC perturbations consistently preceded tropospheric temperature deviations. Importantly, the atmospheric disturbances propagated in the thermosphere as acoustic waves that were generated over the Tonga volcano and on the way between each observation point and the volcano.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study by Shinbori et al. (2023) showed that TEC perturbations consistently preceded tropospheric temperature deviations. Importantly, the atmospheric disturbances propagated in the thermosphere as acoustic waves that were generated over the Tonga volcano and on the way between each observation point and the volcano.…”
Section: Discussionmentioning
confidence: 98%
“…Shinbori et al. (2023) suggested that the pressure waves triggered after the eruption might have propagated well before the propagation of Lamb waves in the ionosphere and generated EPBs over Japan. In addition, there is a sudden increase in electron density and height of the ionosphere before the arrival of the tropospheric perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…(2022) and Shinbori, Sori, et al. (2023) showed the equatorial plasma bubble over the Asia‐Pacific Region after the eruption. Saito (2022) and Liu et al.…”
Section: Introductionmentioning
confidence: 98%
“…Lin et al., 2021) on the ground. Scientists also observe that vertical ground motions of seismic and tsunami waves (Pradipta et al., 2023) as well as volcanic eruptions can trigger disturbances in the atmosphere near the Earth's surface (hereafter termed, traveling atmospheric disturbances (TADs)), which further propagate into the ionosphere (hereafter termed, traveling ionospheric disturbances (TIDs)) (Astafyeva et al., 2022; Shinbori et al., 2023), change the conductivity and the current in the E‐layer at about 110 km altitude (Iyemori et al., 2022; Le et al., 2022; Shinbori et al., 2022), and then modulate underneath magnetic fields on the ground (Liu et al., 2016; Sun et al., 2022).…”
Section: Introductionmentioning
confidence: 99%